MODELING THE GROSS ENROLLMENT RATIO BASED ON DETERMINING FACTORS THROUGH A MIXED-EFFECTS MODEL APPROACH IN INDONESIA: PEMODELAN ANGKA PARTISIPASI KASAR BERDASARKAN FAKTOR-FAKTOR PENENTU MELALUI PENDEKATAN MIXED-EFFECTS MODEL DI INDONESIA - Zhulmuhqsith Busrah; Anna Islamiyati; Erna Tri Herdiani; Danu Raihan Muhammad Faisal (MATHunesa: Jurnal Ilmiah Matematika, 2026)
The Gross Enrollment Ratio (GER) is a key indicator of access to formal education, yet substantial disparities across Indonesian provinces reflect variations in regional socio-economic conditions. This study analyzes the effects of Average Years of Schooling (AYS), Open Unemployment Rate (OUR), and Gross Regional Domestic Product (GRDP) per capita on GER using a Linear Mixed-Effects Model (LMM) based on provincial-level data. The results indicate that OUR has a positive and significant effect on GER (p < 0.001), suggesting that higher unemployment encourages individuals to pursue further education to improve labor market competitiveness. AYS shows a negative but statistically insignificant effect (p > 0.05), implying that educational attainment does not directly translate into increased new participation. GRDP per capita exhibits a positive and significant influence on GER (p < 0.05), highlighting the role of economic capacity in expanding educational access. The Intraclass Correlation Coefficient (ICC) of 0.63 indicates that 63% of the total variation in GER is attributable to provincial-level differences, supporting the appropriateness of the mixed-effects approach. Overall, the findings demonstrate that economic conditions and labor market dynamics are key determinants of educational participation and highlight the need for region-specific policies to address disparities in educational access.